Care-seeking and managing diabetes in rural Bangladesh: a mixed methods study - Hannah Maria Jennings; Joanna Morrison; Kohenour Akter; Hassan Haghparast-Bidgoli; Carina King; Naveed Ahmed; Abdul Kuddus; Sanjit Kumar Shaha; Tasmin Nahar; Kishwar Azad; Edward Fottrell (BMC, 2021)
Abstract Background Type 2 diabetes mellitus poses a major health challenge worldwide and in low-income countries such as Bangladesh, however little is known about the care-seeking of people with diabetes. We sought to understand the factors that affect care-seeking and diabetes management in rural Bangladesh in order to make recommendations as to how care could be better delivered. Methods Survey data from a community-based random sample of 12,047 adults aged 30 years and above identified 292 individuals with a self-reported prior diagnosis of diabetes. Data on health seeking practices regarding testing, medical advice, medication and use of non-allopathic medicine were gathered from these 292 individuals. Qualitative semi-structured interviews and focus group discussions with people with diabetes and semi-structured interviews with health workers explored care-seeking behaviour, management of diabetes and perceptions on quality of care. We explore quality of care using the WHO model with the following domains: safe, effective, patient-centred, timely, equitable and efficient. Results People with diabetes who are aware of their diabetic status do seek care but access, particularly to specialist diabetes services, is hindered by costs, time, crowded conditions and distance. Locally available services, while more accessible, lack infrastructure and expertise. Women are less likely to be diagnosed with diabetes and attend specialist services. Furthermore costs of care and dissatisfaction with health care providers affect medication adherence. Conclusion People with diabetes often make a trade-off between seeking locally available accessible care and specialised care which is more difficult to access. It is vital that health services respond to the needs of patients by building the capacity of local health providers and consider practical ways of supporting diabetes care. Trial registration ISRCTN41083256 . Registered on 30/03/2016.